Multi-axis force sensing using a resonant composite piezoelectric plate: model and experiments. (May 2015) - Castaño-Cano, Davinson; Grossard, Mathieu; Hubert, Arnaud
Abstract Wrist force/torque sensors used in robotic applications increase the performances and flexibility of the automated tasks. They also offer new possibilities in the manufacturing process, where physical contact between the work-piece and environment is required. The wide spreading of these sensors is for now restricted by their features. As an alternative to the existing strain-gauges force sensors, this paper presents a resonant composite structure, which is sensitive to multiple components of force that are considered via the pre-stress effect. Structurally bonded piezoelectric patches are used to bring the structure to its resonance, which is shifted according to applied forces. The relationship between force and frequency shift is modelled considering the multi-physics of this smart structure. This model is built using Hamiltonʼs principle and takes into account pre-stress phenomena. A finite element model (FEM) based on Mindlin theory for plates, has been derived from the analytical model. The FEM model is implemented in MATLAB and compared with commercial FE software. Finally, an experimental prototype validates the model, and shows that it is possible to measure multiple force-components with one single sensing element such as a plate.